Collection development issues of oral history at the National Archives of Zimbabwe. - Ganda, Paidamoyo Purity (Midlands State University, 2017)
Documenting oral history in societies is important because it helps to fill the historical and social gaps in the history of a nation. For effective and efficient documentation of oral history it is important to have stipulated guidelines on what to do and how to do it. These guidelines are found in a collection development policy. . So for effective and efficient documentation of oral history archives ought to have a collection development policy which becomes the foundation upon which their activities are done. The research aimed to establish the good practices that can be employed by NAZ to ensure effective documentation of a total oral history collection. The major research questions were what guides NAZ in documenting oral history. What professional and skills requirements are pre requisite for oral history documentation. The study made use of qualitative research and employed the explanatory design. The author gathered that NAZ has no collection development to guide them in oral history documentation. I also gathered that the unit is facing human resources, financial and equipment challenges because it is a unit which is supposed to cover the whole country. If the National Archives does not formulate a collection development policy they risk being criticised for not effectively documenting oral history. This study concludes that NAZ has not been successful in creating a total oral history archive. Therefore they need to have an oral history collection development policy and find means to raise funds to see to the effective operation of the oral history unit.